2017
DOI: 10.1016/j.rmcr.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical response with increased tumor necrosis factor-α levels to anti-tuberculosis treatment in a patient with disseminated tuberculosis

Abstract: It has been reported that tuberculosis (TB) worsens after cessation of tumor necrosis factor-α inhibitors and starting anti-TB treatment. Little is known about the immunological pathogenesis of this paradoxical response (PR). We report the first case of a TB patient in whom PR occurred concurrently with elevation of circulating tumor necrosis factor-α (TNFα) levels. A 75-year-old woman, who had been treated with adalimumab for SAPHO syndrome, developed disseminated TB. Soon after administration of anti-TB trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Although it has been known that HIV infection is involved with the onset of IRIS, Brown et al reported that immunosuppressive condition decreased the odds ratio of IRIS onset in HIV-negative cases [12]. In recent years, case reports on TB-IRIS upon treatment with anti-TNF-α antibodies have been increased in HIV-negative cases [10,[17][18][19]. In the analysis of patients using anti-TNF-α antibodies against underlying diseases such as rheumatoid arthritis (RA) or Crohn's disease, disseminated TB, past TB infection, and corticosteroid use at the time of diagnosis have been reported as the risk factors of IRIS development [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been known that HIV infection is involved with the onset of IRIS, Brown et al reported that immunosuppressive condition decreased the odds ratio of IRIS onset in HIV-negative cases [12]. In recent years, case reports on TB-IRIS upon treatment with anti-TNF-α antibodies have been increased in HIV-negative cases [10,[17][18][19]. In the analysis of patients using anti-TNF-α antibodies against underlying diseases such as rheumatoid arthritis (RA) or Crohn's disease, disseminated TB, past TB infection, and corticosteroid use at the time of diagnosis have been reported as the risk factors of IRIS development [9].…”
Section: Discussionmentioning
confidence: 99%
“…56 A lethal case of disseminated tuberculosis after discontinuation of adalimumab because of invalidation in a patient with synovitis, acne, pustulosis, hyperostosis and osteitis syndrome has been reported, in whom paradoxical events occurred concurrently with the elevation of circulating TNF-a and a decline in IFN-c levels. 57 If tuberculosis is found during anti-TNF-a therapy, then the anti-TNF-a agent should not be withdrawn because it may lead to severe tuberculosis. TNF-a inhibitors also induce psoriasiform rashes as an adverse event in patients with Crohn's disease and RA.…”
Section: Paradoxical Response During Treatment By Tnf-a Blockadesmentioning
confidence: 99%
“…Because a mild case of IRIS responds to specific treatment for the underlying pathogens, anti‐inflammatory therapies are not generally required. TNF‐α inhibitors and anti‐IL‐6 antibodies can be treatment options for patients with non‐HIV IRIS. Recently, statins have attracted attention as immunomodulators and anti‐inflammatory agents in the management of GVHD.…”
Section: Management Of Non‐hiv Irismentioning
confidence: 99%
“…Treatment of IRIS can at times requires the administration of steroids. However, this approach is not always successful and there have been reports of patients who present with a severe inflammatory response during the treatment of TB or fungal infections that appear to be steroid-refractory and require other treatment options [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%